The Effect of Clarity on Budget Targets and Reporting Systems on Performance Accountability with Internal Controls as Intervening Variables in the SKPD of the Kotabaru Regency Government - Sanusi Sanusi; Padlah Riyadi (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to examine the clarity of budget targets and reporting systems that affect performance accountability. This study also examines whether the internal control system mediates the effect of the clarity of budget targets and the reporting system. This study is of the type of associative causality and is carried out through a survey method by distributing questionnaires to the compilers of the performance accountability report of government agencies in Kotabaru. The population of this study was all SKPD in the Kotabaru Regency Government, totaling 30 SKPD consisting of 82 sample respondents. This study uses descriptive statistical analysis and partial least squares (SEM-PLS) analysis. Analysis powered by Smart-PLS 3.0. The results of this study show that the clarity of budget targets and internal controls affect the performance accountability of government agencies, while the reporting system does not affect performance accountability. Clarity of budget targets, and reporting systems affect internal control. Internal control as an interverning variable can affect the clarity of budget objectives and reporting systems on performance accountability.